Precision Endonasal Endoscopic Surgery of the Frontal Recess Cells and Frontal Sinus Guided by the Natural Sinus Drainage Pathway - Peng, Zhouying; Wang, Yumin; Fang, Yan; Wang, Yaxuan; Chen, Xiang; Fan, Ruohao; Zhang, Hua; Xie, Zhihai; Jiang, Weihong (Frontiers in Surgery, 2022)
Background The endoscopic endonasal approach to removing lesions in the nasal cavity and sinuses has become the modern first choice. However, if endoscopic surgery is performed without proper knowledge of sinus anatomy, there is a risk of residual lesions, recurrence, and even serious complications. Therefore, this article illustrates the importance of precise sinus opening guided by the natural sinus drainage pathway, using the anatomy of the frontal sinus (FS) and the frontal recess (FR) cells as an example. Method A total of 82 sides cadaveric heads were dissected and analyzed, and the natural drainage pathways of the FR cells and FS were observed at 0°and 70°nasal endoscopic views, and the findings were summarized. The data of 79 patients who accepted endonasal endoscopic surgery (EES) guided by natural sinus drainage pathways to remove mucoceles in our department from January 2015 to January 2021 were retrospectively analyzed. Results Two natural drainage pathways of the FR cells were discovered, identified, and named the medial pathway of the FR (MPFR) and the lateral pathway of the FR (LPFR). The 79 patients who accepted EES to remove mucoceles through the natural drainage pathways of FR cells and the FS showed significant improvement in clinical symptoms, and none of them had recurrence after surgery without serious complications. Conclusion The EES of the FR cells and FS through the natural drainage pathways to remove the mucoceles facilitates exposure of the cells without residual lesions and without serious complications.